Surgical treatment of cervical spine trauma: Our experience and results - Dobran, Mauro (Asian J Neurosurg, 2015)
OBJECTIVE AND BACKGROUND: The objective of this study is to evaluate how the neurological outcome in patients operated for cervical spinal cord injury (SCI) is influenced by surgical timing, admission American Spinal Injury Association (ASIA) grading system, and age. MATERIALS AND METHODS: From January 2004 to December 2011, we operated 110 patients with cervical SCI. Fifty-seven of them (44 males and 13 females) with preoperative neurological deficit, were included in this study with a complete follow-up. Age, sex, associated comorbidities (evaluated with Charlson comorbidity index [CCI]), mechanism of trauma, preoperative and follow-up ASIA score, time elapsed from injury to surgical treatment, preoperative cervical computed tomography scan or magnetic resonance imaging, type of fractures, and surgical procedure were evaluated for each patient. The patient population was divided into two groups related to the timing of surgery: Ultra-early surgery group (within 12 h from the trauma, 27 patients) and early surgery (within 12–72 h from the trauma, 30 patients). STATISTICAL ANALYSIS USED: The univariate analysis of data was carried out by the Chi-square test for discrete variables, the t-test for the continuous ones. Logistic regression was used for the multivariate analysis. RESULTS: Neurological outcome was statistically better in ultra-early surgery group (<12 h) than in patient underwent surgery within 12–72 h (82.14% vs. 31%, multivariate analysis P = 0.005). The neurological improvement was also correlated with the age and the ASIA grade at admission in the univariate analysis (P = 0.006 and P = 0.017 respectively) and in the multivariate 1 (P = 0.037 and P = 0.006 respectively) while the CCI was correlated with the improvement only in the univariate analysis (P = 0.007). CONCLUSION: Nowadays, in patients with cervical SCI early surgery could be associated with improved outcome, most in case of young people with mild neurological impairment.